Early retirement and social security : a long term perspective - Jose Ignacio Conde-Ruiz; Vincenzo Galasso; Paola Profeta (Center for Economic Studies and ifo Institute (CESifo), 2005)
We provide a long-term perspective on the individual retirement behaviour and on the future of retirement. In a Markovian political economic theoretical framework, in which incentives to retire early are embedded, we derive a political equilibrium with positive social security contribution rates and early retirement. Aging has two opposite effects: it leads to lower taxes and fewer (early) retirees, while a poorer median voter will push for higher contributions. The model highlights the existence of crucial income effects: a decrease of the income of young people will induce them to postpone retirement and to vote for less social security.
Keywords: H55; D72; H53; 330; pensions; income effect; tax burden; politico-economic Markovian equilibrium; Flexible Altersgrenze; Soziale Sicherung; Sozialversicherungsbeitrag; Public Choice; Einkommenseffekt; Alternde Bevölkerung; Theorie